Risk factors for postpartum maternal mortality and hospital readmission in lowand middle‑income countries: a systematic review - Symonds, Nicola E.; Vidler, Marianne; Wiens, Matthew O.; Omar, Shazmeen; English, L. Lacey; Ukah, U. Vivian; Ansermino, J. Mark; Ngonzi, Joseph; Bebell, Lisa M.; Hwang, Bella; Christoffersen‑Deb, Astrid; Kissoon, Niranjan; et al. (BMC Pregnancy and Childbirth, 2023)
Background: In low- and middle-income countries, approximately two thirds of maternal deaths occur in the postpartum period. Yet, care for women beyond 24 h after discharge is limited. The objective of this systematic review is to summarize current evidence on socio-demographic and clinical risk factors for (1) postpartum mortality and (2) postpartum hospital readmission. Methods: A combination of keywords and subject headings (i.e. MeSH terms) for postpartum maternal mortality or readmission were searched. Articles published up to January 9, 2021 were identified in MEDLINE, EMBASE, and CINAHL databases, without language restrictions. Studies reporting socio-demographic or clinical risk factors for postpartum mortality or readmission within six weeks of delivery among women who delivered a livebirth in a low- or middle-income country was included. Data were extracted independently by two reviewers based on study characteristics, population, and outcomes. Included studies were assessed for quality and risk of bias using the Downs and Black checklist for ratings of randomized and non-randomized studies. Results: Of 8783 abstracts screened, seven studies were included (total N = 387,786). Risk factors for postpartum mortality included Caesarean mode of delivery, nulliparity, low or very low birthweight, and shock upon admission. Risk factors for postpartum readmission included Caesarean mode of delivery, HIV positive serostatus, and abnormal body temperature. Conclusions: Few studies reported individual socio-demographic or clinical risk factors for mortality or readmission after delivery in low- and middle-income countries; only Caesarean delivery was consistently reported. Further research is needed to identify factors that put women at greatest risk of post-discharge complications and mortality. Understanding post-discharge risk would facilitate targeted postpartum care and reduce adverse outcomes in women after delivery.
Keywords: Postpartum period; Maternal mortality; Readmission; Post-discharge risk; Low- and middle-income countries